A study on the bacteriological quality of water from the dental unit waterline in the operative dentistry, oral medicine, and oral surgery clinics of the UP College of Dentistry - Cueto, Beverly M.
This study aimed to determine the bacteriological quality of the water from the waterlines in the dental units of the Operative Dentistry, Oral Medicine, and Oral Surgery clinics of the UP College of Dentistry. Oral dental unit was randomly chosen from the Operative Dentistry (OP), Oral Medicine (OM), and Oral Surgery (OS) clinics for collection of waterline tubes and water samples. The external surface of the cup filler and three-way syringe/handpiece tubes were disinfected, and cut and placed in sterile container (with water) and then cultured for bacteria and subjected to biochemical tests for identification. Water samples were taken from the cup filler, three-ways syringe, and tap then analyzed with Multiple Tube Fermentation Technique. Results showed that Enterobacter agglomerans were present in the tubes from the three-ways syringe from the OP and OS clinics and Klebsiella pneumoniae in the OM clinic. The tubes from the cup fillers all contain gram-positive cocci. Water analysis revealed that the water taken from the cup fillers, three-ways syringe and tap were bacteriologically potable except or the sample taken from three-way syringe in OS. Therefore, the water used in the Operative Dentistry, Oral Medicine,and Oral Surgery clinics in UP College of Dentistry Building is bacteriologically potable and fit for consumption during dental treatment.